Urinary incontinence related to perineal muscle strength in the first trimester of pregnancy: cross-sectional study - Maria Luiza Gonzalez Riesco; Karina Fernandes-Trevisan; Nathalie Leister; Camila da Silva Cruz; Adriana de Souza Caroci; Miriam Raquel Diniz Zanetti (SciELO, 2014)
Objective To analyze pelvic floor muscle strength (PFMS), urinary continence and quality of life related to urinary incontinence (UI) of women in the first trimester of pregnancy. Method Cross-sectional study with a sample of 500 women who started prenatal care in a complementary healthcare facility in Guarulhos, state of São Paulo, from 2012 and 2013. Pelvic floor muscle strength was evaluated through perineometry. The pregnant women who presented UI answered the International Consultation on Incontinence Questionnaire-Short Form (ICIQ-SF). Results It was found that maternal age (OR=1.06; CI95% 1.02-1.11) and prior UI (OR=15.12; 95%CI 8.19-27.92) are the variables that, in tandem, best explain the occurrence of UI at the beginning of pregnancy. The mean score on the ICIQ-SF was 8.2 (SD=3.9), considered a moderate impact on quality of life. Conclusion Older pregnant women with prior UI are more likely to have UI in the first trimester of pregnancy.